Additive manufacturing polyurethane acrylate via stereolithography for 3D structure polymer electrolyte application - Norjeli, Muhammad Faishal; Tamchek, Nizam; Osman, Zurina; Mohd Noor, Ikhwan Syafiq; Kufian, Mohd Zieauddin; Mohd Ghazali, Mohd Ifwat (Multidisciplinary Digital Publishing Institute, 2022)
Additive manufacturing (AM), also known as 3D-printing technology, is currently integrated in many fields as it possesses an attractive fabrication process. In this work, we deployed the 3D-print stereolithography (SLA) method to print polyurethane acrylate (PUA)-based gel polymer electrolyte (GPE). The printed PUA GPE was then characterized through several techniques, such as Fourier transform infrared (FTIR), electrochemical impedance spectroscopy (EIS), X-ray diffraction analysis (XRD), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and scanning electron microscope (SEM). The printed GPE exhibited high ionic conductivity of 1.24 × 10−3 S cm−1 at low-lithium-salt content (10 wt.%) in ambient temperature and favorable thermal stability to about 300 °C. The FTIR results show that addition of LiClO4 to the polymer matrix caused a shift in carbonyl, ester and amide functional groups. In addition, FTIR deconvolution peaks of LiClO4 show 10 wt.% has the highest amount of free ions, in line with the highest conductivity achieved. Finally, the PUA GPE was printed into 3D complex structure to show SLA flexibility in designing an electrolyte, which could be a potential application in advanced battery fabrication.